2017
DOI: 10.4028/www.scientific.net/ssp.260.99
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Different Gas Influence for Operation of Modified Atomic Force Microscope Sensor

Abstract: This paper presents modelling of various gas application to modified atomic force microscope sensor in order to change its existing dynamic characteristics. This paper represents part of continuous research, which is focused on improvement of scanning speed of atomic force microscope (AFM) sensor. Subject of our research is enhancement of dynamic characteristics of Atomic force microscope sensor. Natural frequency of AFM sensor is the main factor influencing max scanning speed of atomic force microscope. In ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The parameters of the aerodynamic force were determined from the theoretical 3D model of the microscope cantilever, as reported previously [ 17 ]. This model describes the dependencies among the air gap, the pressure of compressed air, and the resulting force on the cantilever.…”
Section: Dynamic Model Of the Afm Cantilevermentioning
confidence: 99%
See 2 more Smart Citations
“…The parameters of the aerodynamic force were determined from the theoretical 3D model of the microscope cantilever, as reported previously [ 17 ]. This model describes the dependencies among the air gap, the pressure of compressed air, and the resulting force on the cantilever.…”
Section: Dynamic Model Of the Afm Cantilevermentioning
confidence: 99%
“…This model describes the dependencies among the air gap, the pressure of compressed air, and the resulting force on the cantilever. The displacement of the cantilever at coordinate η 2 ( Figure 1 ) defined from results of finite element modelling (FEM) analysis [ 17 ] and approximated by polynomial in respect to relative gap and expressed in terms of our model, is: η 2 = −0.0007·(Δ 0 − η 1 ) 3 + 0.0033·(Δ 0 − η 1 ) 2 + 0.0063·(Δ 0 − η 1 ) + 0.0049 …”
Section: Dynamic Model Of the Afm Cantilevermentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters of the aerodynamic force were determined using our previous research results from the theoretical 3D model of the microscope cantilever [17]. This model provided the dependencies among the air gap, the pressure of compressed air and the resulting force on the cantilever.…”
Section: General Considerationsmentioning
confidence: 99%
“…For the introduction of the airflow to the microscope it is enough to produce a cantilever holder with an installed micro air duct and a precise airflow control system. In earlier research, it was found that the AFM cantilever is sensitive to air stream [12,17]. The effect of an applied aerodynamic force depends on: initial gas pressure, air duct diameter and shape, initial gap size between air duct and cantilever surface.…”
Section: Introductionmentioning
confidence: 99%